Mott-Hubbard exciton in the optical conductivity of YTiO 3 and SmTiO 3 - Gössling, Alexander; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2008)
In the Mott-Hubbard insulators YTiO3 and SmTiO3 we study optical excitations from the lower to the upper Hubbard band, ∣∣d1d1⟩→∣∣d0d2⟩. The multipeak structure observed in the optical conductivity reflects the multiplet structure of the upper Hubbard band in a multiorbital system. Absorption bands at 2.55 and 4.15 eV in the ferromagnet YTiO3 correspond to final states with a triplet d2 configuration, whereas a peak at 3.7 eV in the antiferromagnet SmTiO3 is attributed to a singlet d2 final state. A strongly temperature-dependent peak at 1.95 eV in YTiO3 and 1.8 eV in SmTiO3 is interpreted in terms of a Hubbard exciton, i.e., a charge-neutral (quasi-) bound state of a hole in the lower Hubbard band and a double occupancy in the upper one. The binding to such a Hubbard exciton may arise both due to Coulomb attraction between nearest-neighbor sites and due to a lowering of the kinetic energy in a system with magnetic and/or orbital correlations. Furthermore, we observe anomalies of the spectral weight in the vicinity of the magnetic ordering transitions, both in YTiO3 and SmTiO3. In the G-type antiferromagnet SmTiO3, the sign of the change of the spectral weight at TN depends on the polarization. This demonstrates that the temperature dependence of the spectral weight is not dominated by the spin-spin correlations, but rather reflects small changes of the orbital occupation.